Role of preoperative magnetic resonance imaging and histological assessment in identifying patients with a low risk of endometrial cancer: a Korean Gynecologic Oncology Group ancillary study - Lee, Jung-Yun (Oncotarget, 2017)
Preoperative identification of individuals at low risk of lymph node metastasis is key to the proper management of endometrial cancer. This study evaluated the role of preoperative assessment based on magnetic resonance imaging (MRI) and histological analysis in identifying a group having a low risk of lymph node metastasis. Data of 529 patients with endometrial cancer were obtained from a prospective multicenter database, between January 2012 and December 2014. Clinical staging, based on MRI and histological analysis, was compared with final pathology results after the surgical staging procedure. The preoperative low-risk criteria, based on current guidelines from Korea, France, and Canada, and criteria used for fertility-sparing therapies, were applied to our multicenter cohort and the accuracy of each set of criteria for identifying group at low risk of lymph node metastasis was evaluated. When considering grades or MR stages separately, the overall agreement between preoperative and postoperative findings was poor (Kappa 0.45 for grades; 0.41 for stages). However, when combining these two parameters, the low-risk group, as defined by any of the guidelines, had an acceptable rate of lymph node metastasis (below 3%). The French guidelines identified 249 patients (47.1%) as being in the low-risk group. Criteria used to define fertility-sparing therapy candidates identified 48 patients (9.1%) among the study population, only one of whom had extra-uterine disease. This study shows that the current guidelines, using preoperative assessment based on MRI and histological analysis, can identify low-risk patients, who may be candidates for omitting lymphadenectomy.